2004
DOI: 10.1017/s0021859604004022
|View full text |Cite
|
Sign up to set email alerts
|

Use of CERES-Wheat model for wheat yield forecast in central Indo-Gangetic Plains of India

Abstract: A methodology was developed for large area yield forecast using a crop simulation model and a discrete technology trend, and was applied to the coherent wheat yield variability zones of Eastern Uttar Pradesh, India. The approach consisted of three major steps: (a) prediction of technology trend yield using historical yield series of the region; (b) prediction of weather-induced deviation in wheat yield using CERES-Wheat simulation model and relating weather-induced deviation in simulated yield to deviation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
(16 reference statements)
2
12
0
Order By: Relevance
“…Our results demonstrated reasonable accuracy for yield simulation even over several wheat growth seasons. This result was consistent with Nain et al (2004), Ahmad et al (2012), and Thorp et al (2012). The DSSAT-CERES model is a process-based model that can capture the nonlinear interannual variability in crop yield, due to the consideration of interannual variations in weather conditions, management strategies, and the interactions between the two (Nain et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results demonstrated reasonable accuracy for yield simulation even over several wheat growth seasons. This result was consistent with Nain et al (2004), Ahmad et al (2012), and Thorp et al (2012). The DSSAT-CERES model is a process-based model that can capture the nonlinear interannual variability in crop yield, due to the consideration of interannual variations in weather conditions, management strategies, and the interactions between the two (Nain et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…For wheat, the AgMIP (Agricultural Model Intercomparison and Improvement Project) listed 27 representative wheat models around the world (Asseng et al, 2013). The decision support system for agrotechnology transfer (DSSAT) including the CERES-Wheat model has been widely used over the last 25 years by many researchers for many different applications, and it has been shown to be capable of robust yield predictions across various environmental, soil, and management strategy conditions (Landau et al, 1998;Jones et al, 2003;Nain et al, 2004;Fang et al, 2008;Thorp et al, 2010;Liu et al, 2011;Huffman et al, 2015). When applied over a large-scale area, however, the model has shown low prediction performance because the boundary conditions (soil, management) are often poorly known and model parameters are uncertain (Moulin et al, 1998;Dorigo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The value of R 2 was 80.60% which is significant at 1% level of significance. Nain et al, (2004) also reported that the differences between observed and predicted wheat yield were, on an average, 4.72% by using weather variables for IndoGangetic plains. Likewise, yield of groundnut was significantly correlated with growing season rainfall in southern India Gadgil et al, (2002).…”
Section: Effect Of Minimum Temperaturementioning
confidence: 96%
“…The use of this technique is not unique to southern Africa as the model has been used in many parts of the world to assess national food security and provide early food shortage warning (Reynolds et al 2000). Early assessment of yield helps in strategic planning and decision making (Nain et al 2002, Nain et al 2004Domenikiotis et al 2004), and the longer the lead time for the postplanting yield forecasts the better.…”
Section: Introductionmentioning
confidence: 99%